Financial Education, Parent's Income, Financial Literacy on Financial Management Behavior through Self-Financial Efficacy in Students - Muhammad Syarifuddin Ahzab; Dies Nurhayati; Etta Mamang Sangadji (CV. AFDIFAL MAJU BERKAH, 2023)
Globalization is marked by the rapid advancement of technology, which will impact human thinking patterns and tend to encourage individuals to get trapped in consumer behavior. The lack of financial literacy makes society vulnerable to financial problems. Therefore, the importance of the role of both the community and the government in providing education on financial literacy is crucial. One of the government's roles, through OJK, is to provide education on Financial Literacy to the public, especially students and scholars. The community's role can start from within the family circle, by educating children about family financial management from an early age. Consequently, financial education from a young age will inadvertently benefit children because they can manage their finances, such as pocket money, effectively. The methods used include quantitative methods combined with path analysis, and the results show that there is a direct influence of Family Financial Education, Parent's Income, and financial knowledge on financial management behavior through self-financial efficacy. Then, the results of the Path Analysis with the Sobel test show that Family Financial Education (0.495 > 0.387), Parent's Income (0.158 > -0.194), and Financial Literacy (0.176 > -0.289) affect these variables. The conclusion from the test results indicates that Family Financial Education, Parent's Income, and Financial Literacy directly and indirectly influence the financial behavior patterns of students.